Persepsi Peternak Terhadap Kinerja Penyuluh di Desa Maubesi Kecamatan Insana Tengah Kabupaten Timor Tengah Utara - Maria Fatima Kosat; Ture Simamora; Jefrianus Neonnub; Maria Magdalena Kapitan (Universitas Respati Indonesia, 2025)
This study aims to determine the characteristics of livestock farmers in Maubesi Village, Insana Tengah District, North Central Timor Regency and to determine the perception of livestock farmers towards the performance of livestock extension workers in Maubesi Village, Insana Tengah District, North Central Timor Regency. This study was conducted from August to September 2024 in 3 Farmer Groups in Maubesi Village. This study was conducted using a survey method and direct observation in the field using a questionnaire with a total of 65 respondents. The sampling method in this study used purposive sampling with the criteria of groups that were active in extension activities. The type of data analysis in this study is descriptive and percentage data analysis with data collection techniques carried out through the distribution of questionnaires in the form of a Likert scale, interviews, observations, and recording. The results of the study can be concluded that the characteristics of respondents based on the age of respondents are dominated by the productive age category (15-60) as many as 44 people (67,7%), the level of education of respondents is dominated by the level of education is still very low or 15 years as many as 44 people (67,7%), livestock ownership of most respondents has livestock of 3 or less as many as 35 people (53.8%) and the number of family dependents is dominated by 3-4 people as many as 25 people (38.5%). Meanwhile, the extension material has a good perception with the very pus and satisfied categories which are more dominant than 65 respondents in Maubesi Village, Insana Tengah District, North Central Timor Regency, so that it helps respondents in managing their livestock, for the media and extension methods, respondents are dominated by the very satisfied category with an average value of 89,7% and the results of the extension worker's performance can be seen from the responsiveness with an average value of 68,8%, responsibility 81,5% and quality of service with an average value of 76,9% carried out by extension workers in Maubesi Village, Insana Tengah District, North Central Timor Regency. The conclusion of this study is that respondents feel very satisfied with the performance of the extension workers.